Repellent activity of DEET against Amblyomma cajennense (Acari: Ixodidae) nymphs submitted to different laboratory bioassays - Soares,Sara Fernandes (2010)
This study was developed to evaluate the repellent activity of N,N-diethyl-3-methylbenzamide (DEET) against Amblyomma cajennense nymphs. Two repellent bioassays were compared and the effective concentration and repellent time were calculated. The fingertip test was accomplished to evaluate in vivo four concentrations of the compound (0.200; 0.100; 0.050 and 0.025 mg.cm-2) and the filter-paper bioassay to evaluate in vitro the two highest concentrations. The compound provided repellence higher than 90% in all concentrations and at least 95% repellency in the highest concentration over 5 hours. The effective concentration against 50% of tested nymphs (EC50) was 0.006 mg.cm-2 and the EC99 was 0.036 mg.cm-2. Those concentrations were lower than the ones obtained against other tick species, denoting the effectiveness of DEET against A. cajennense. The repellency time against 50% of the ticks (RT50) was 4.8 hours and the RT90 was 2.7 hours. Both bioassays were adequate to evaluate A. cajennense repellency and provided similar results; however the in vivo test is more appropriate to estimate the effective concentration and repellency time.